PREFERRED STRATEGIES USED BY PEKANBARU SENIOR HIGH SCHOOL STUDENTS’ TO LEARN INDIVIDUAL SKILLS Of ENGLISH - Fakhri Ras (International Conference on Languages and Arts, 2012)
The  objective of this study is to investigate how Pekanbaru senior high school students learn various language skills (listening, speaking, reading, writing as well as vocabulary and structure). One of the definitions of language learning strategies is defined by Oxford (1990b). She states that language learning strategies are specific actions taken by the learners to make learning easier, faster, more enjoyable, more self-directed, more efficient, and more transferable in new situation. The needed data were collected by interviewing 10 selected students from five ethnic groups (Malay, Minangkabau, Javanese, Batak, and Chinese) at various senior high schools in Pekanbaru.   The respondents were asked to answer the following question: If you are asked to increase the the four language skills (listening, speaking, reading, writing as well as vocabulary and structure),  what do you do? Inter-rater reliability was used to judge the answers of related respondents in the interview by the qualified inter-raters-that are master’s degree in TEFL. The inter-raters modified the respondents’ responses in casual English into acceptable written English without changing the concept of the expression. The highest frequency has been acknowledged. There are 67 strategies identified as the most-preferred strategies employed by the respondents to increase the language skills as well as vocabulary  and structure. The use of these strategies can be grouped into once-mentioned, twice-mentioned, and more than twice-mentioned. Examples of strategies mentioned more than twice for improving for improving speaking skills, preparing as much vocabulary as possible (four times); and for improving writing skill, the strategy of writing procedurally (three times). Suggestions for further study are those the successful learners, less successful learners, and gifted learners should also be taken into account as crucial factors to investigate in the near future. Key words: learning, language learning strategy, language skill